2017
DOI: 10.12659/msm.902728
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Improves Spatial Learning and Memory in Vascular Dementia Rats with Activation of Wnt/β-Catenin Signal Pathway

Abstract: BackgroundEnvironmental enrichment (EE) has a beneficial effect on some neuropsychiatric disorders. In this study, we aimed to investigate whether environmental enrichment could improve the spatial learning and memory in rats with vascular dementia (VaD) and the mechanism underpinning it.Material/MethodsBilateral common carotid occlusion (2-vessel occlusion [2VO]) was used to develop the animal model of vascular dementia. Adult male Sprague-Dawley (SD) rats were used in the experiment and were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…Thus, we have provided novel molecular mechanisms of EE in the context of RTT. These results are also congruent with another report showing that EE improves memory function in vascular dementia rats associated with activation of Wnt3a signaling 29 . It is conceivable that EE activates many more genes other than Wnt6, yet EE could not completely rescue the behavioral deficits of MeCP2 T158A mice.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we have provided novel molecular mechanisms of EE in the context of RTT. These results are also congruent with another report showing that EE improves memory function in vascular dementia rats associated with activation of Wnt3a signaling 29 . It is conceivable that EE activates many more genes other than Wnt6, yet EE could not completely rescue the behavioral deficits of MeCP2 T158A mice.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies using environmental enrichment, they have shown to improve spatial memory in the Morris water maze test [11,12];…”
Section: Discussionmentioning
confidence: 99%
“…In other words, environmentally enriched housing helped improve their stress-coping strategies [10]. Regarding spatial learning and memory, environmental enrichment showed positive effect by reducing the escape latencies in the Morris water maze test [11,12].…”
Section: Effect Of Environmental Factors On Depressive-like Behavior mentioning
confidence: 99%
“…Although more studies are needed to understand why RA treatment makes SH-SY5Y cells more sensitive to Ni and more resistant to Cr, these two heavy metals may induce neuronal death by different mechanisms. Cr and Ni have opposite effects in the regulation of the PI3K/AKT survival signaling pathway, Cr treatment inhibits PI3K/AKT activity 66 while Ni exposure activates the pathway 67 . RA treatment induces the activation of survival pathways including PI3K/AKT in SH-SY5Y cells 61 , thus we speculate that the addition of RA could be protecting the neuron-like differentiated SH-SY5Y cells from toxicity induced by Cr but sensitizing them to the cell death induced by Ni.…”
Section: Discussionmentioning
confidence: 99%